The Implementation of a Social Marketing Approach for Rainwater Harvesting and Preservation - Dsouza, Divya Kiran (Digital Repository of Theses - SSBM Geneva, 2025)
Water crisis is identified as one of the biggest global threats due to its potential impacts on the environment and the ecosystem. Global warming, shifting climatic conditions, and rising populations, poses a substantial risk to urban water supply in developing countries. As a fundamental resource for human survival amidst changing climate conditions, water serves as a vital elixir that sustains life and ecosystems. Rainwater harvesting has been identified to be an optimal solution for water crisis all over the world. India, being a sub-tropical country, receives an ample amount of rain. However, most of the Indian states are recently facing severe challenges of water scarcity. This scenario is likely to worsen in the impending years, due to the anticipated severity of climate change. Therefore, it is it is necessary to understand the determinants that influence residents’ adoption of rainwater harvesting and enhance awareness about its usage. Moreover, previous studies indicate that while awareness programs and campaigns motivate users to express an intention to adopt RWH, the actual installation of such systems remains limited. Therefore, an exploration of extensive studies on perceptions of Indian users is required to comprehend the behavioral nuances surrounding the use of rainwater harvesting structures. Following a thorough review of present literature, a conceptual framework has been constructed for the present study based on the research gaps found. The theoretical basis of this study is an integrated Motivation-Opportunity-Ability (MOA) framework which incorporates the Theory of Planned Behavior (TPB) to investigate the determinants of RWH behavior. The study adopted a positivistic research philosophy along with a descriptive and explanatory research purpose. A quantitative research approach with cross-sectional nature was chosen where close-ended structured questionnaire was used for data collection with a stratified sampling method. The target population for the study was the urban residents from one of the fastest growing cities in India, Bengaluru. After going through a pilot analysis, the final questionnaires were sent to 600 residents in Bengaluru and out of these 400 were selected as study participants. The study revealed that majority of the residents in the study were male and belonged to the age group between 25-45 years old. Most of them were graduates. They mostly lived in individual house or multi-storied flat, however it was dominantly rented accommodations. Independent t-test and ANOVA results showed that belief, attitude, subjective norms, motivation, barriers, ability and opportunity were significantly different for various sociodemographic factors. Linear regression analysis showed that belief, attitude and subjective norms significantly influenced the behavioral intention of the participants. Furthermore, the study showed that behavioral intention, motivation, opportunity, ability and barriers significantly influenced actual usage of RWH in their houses. In addition, PLS-SEM demonstrated that motivation, opportunity, ability and barriers significantly moderated the relationships between behavioral intention and actual adoption of RWH. While motivation, opportunity, ability positively moderated the association between behavioral intention and actual adoption of RWH, barriers negatively moderated the association. The study potentially provides several theoretical, managerial, and societal implications on social marketing theme and provides extensive comprehension on urban residents’ perception regarding rainwater harvesting. The study further provides several recommendations for policymakers and administrators on constructing strategies for increased acceptance of rainwater harvesting in other developing countries.